The Role Of E-Commerce Era Covid-19 in The Revolution Of The Accounting Information Systems - Lesi Hertati (Jambura Science of Management, 2021)
The purpose of this study is to determine the effect of e.commmerce Era Covid-19, Corporate Strategy in the Covid-19 era on the accounting information system industrial revolution. The company's strategy is a company trick in determining and expressing the main planning policies that ultimately determine the scope, character and results of the company's activities and their parts to achieve the company's goals. The fact states that the influence of e.commerce, the company's strategy has various problems including the problem of collecting and storing data on organizational activities, resources and personnel, converting data into information so that management can plan, implement, control and evaluate activities, resources and personnel, provide adequate controls for storing organizational assets and data. The population of this research is 7000 employees of PT Freeport Indonesia, with a total sample of 852 employees obtained through simple random sampling. The purpose of this study is to determine the use of E-Commerce in the Covid-19 Era, the company's strategy in the Industrial Revolution accounting information system. This method is a descriptive and verification method, and the analytical tool is SEM Lisrel modeling. The results showed that E-Commerce is a company strategy in the Industrial Revolution in accounting information systems.